Mineralization of Soil Organic Nitrogen Under Waterlogged Conditions in Relation to Other Properties of Tropical Rice Soils - Sahrawat, K.L. (Commonwealth Scientific and Industrial Research Organisation, 1983)
The mineralizable nitrogen pool in wetland rice soils plays a dominant role in the nitrogen nutrition of rice even in fertilized paddies. There is a lack of information on how different soil properties affect ammonification of organic nitrogen in wetland rice soils. Surface samples of 39 diverse Philippine soils representing a wide range of pH, organic matter and texture were studied to determine the relationships between ammonification of organic nitrogen and soil properties. Simple correlation analysis showed that ammonium production was correlated highly significantly with total nitrogen (r = 0.94**), organic carbon (r = 0.91**) and C/N ratio (r = -0.46**), but it was not significantly correlated with cation exchange capacity, clay or pH. Multiple regression analayses showed that organic matter (organic carbon and total nitrogen) accounted for most of the variation in mineralizable nitrogen. These results suggest that organic carbon content is a good index of mineralizable nitrogen in tropical wetland rice soils.